In-vehicle monitoring - Hutchinson, Nicholas Dunkley (2020)
In a method of video monitoring of a subject, for example a driver of a vehicle, the video image is motion compensated by image registration techniques so that the subject's position in each frame of the video image is stable. A region of interest is defined on the skin of the subject and used to obtain a PPG signal. To compensate for variations in illumination of the subject caused by the subject's movement in the vehicle, the parameters of the calculated motion transformation used in the image registration are used to form an illumination model representing how the illumination of the subject would have changed because of the subject's motion. The illumination model is a linear or quadratic function fitted to the image intensity in the region of interest. Residuals between the fitted model and the image intensity form an illumination-compensated signal in which the photoplethysmographic signal is more clearly present. The illumination-compensated signal is analysed to obtain a PPG signal and from this estimates of one or more vital signs such as heart rate or breathing rate are obtained.